2019
DOI: 10.1051/0004-6361/201935137
|View full text |Cite
|
Sign up to set email alerts
|

VIS3COS

Abstract: We study the impact of local density and stellar mass on the structure and morphology of approximately 500 quiescent and star-forming galaxies from the VIMOS Spectroscopic Survey of a Superstructure in COSMOS (VIS3COS). We perform bulge-to-disc decomposition of the surface brightness profiles and find ∼41 ± 3% of > 1010 M⊙ galaxies to be best fitted with two components. We complement our analysis with non-parametric morphological measurements and qualitative visual classifications. We find that both galaxy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 175 publications
(240 reference statements)
8
19
0
Order By: Relevance
“…Results tend to agree that higher density environments increase the fraction of quiescent (red) galaxies and we do see this in the COSMOS field (see top right panel of Figure 28; Peng et al 2010;McGee et al 2011;Scoville et al 2013;Darvish et al 2014Darvish et al , 2016. Whether or not the normalization of the MS (defined for starforming galaxies) depends on galaxy environment is still under debate, but many studies identify no variations of MS with environments such as clusters and voids, e.g., Tyler et al (2013), Koyama et al (2014), Ricciardelli et al (2014), Tyler et al (2014), Grossi et al (2018), Paulino-Afonso et al (2019), Pharo et al (2020 (although see Duivenvoorden et al 2016 who found a difference at 1.5 < z < 2 in COSMOS). However, at low redshift (z < 0.3), studies have reported a clear dependence of the MS on galaxy environment (e.g., von der Linden et al 2010, Haines et al 2013, Gu et al 2018, Paccagnella et al 2016).…”
Section: Environmental Trendssupporting
confidence: 73%
See 1 more Smart Citation
“…Results tend to agree that higher density environments increase the fraction of quiescent (red) galaxies and we do see this in the COSMOS field (see top right panel of Figure 28; Peng et al 2010;McGee et al 2011;Scoville et al 2013;Darvish et al 2014Darvish et al , 2016. Whether or not the normalization of the MS (defined for starforming galaxies) depends on galaxy environment is still under debate, but many studies identify no variations of MS with environments such as clusters and voids, e.g., Tyler et al (2013), Koyama et al (2014), Ricciardelli et al (2014), Tyler et al (2014), Grossi et al (2018), Paulino-Afonso et al (2019), Pharo et al (2020 (although see Duivenvoorden et al 2016 who found a difference at 1.5 < z < 2 in COSMOS). However, at low redshift (z < 0.3), studies have reported a clear dependence of the MS on galaxy environment (e.g., von der Linden et al 2010, Haines et al 2013, Gu et al 2018, Paccagnella et al 2016).…”
Section: Environmental Trendssupporting
confidence: 73%
“…Using the local density as probed by the number Mpc −2 and 80 Mpc −2 are the minimum and maximum values in the catalog). These very roughly trace void, field, filament and group, and cluster environments(Paulino-Afonso et al 2019). Figure12shows no statistically significant difference be-…”
mentioning
confidence: 88%
“…As galaxies fall into the cluster, gas is stripped off through ram pressure stripping (Gunn & Gott III 1972;Balogh et al 2004;Hester 2006;Cortese & Hughes 2009;Nichols & Bland-Hawthorn 2011;Brown et al 2017;Gupta et al 2017), resulting in a gradual decline in the SFR as galaxies run out of their star formation fuel (strangulation; Peng et al 2015;Bahé & Mc-Carthy 2015;Wang et al 2018). Both simulations and observational studies find evidence of lower star formation in cluster galaxies compared to field galaxies up to z ∼ 2 (Lewis et al 2002;Mcgee et al 2011;Rasmussen et al 2012;Tran et al 2015;Paccagnella et al 2016;Bahé et al 2017;Genel et al 2018;Sobral et al 2016;Darvish et al 2016Darvish et al , 2017Muzzin et al 2012;Davies et al 2019;Paulino-Afonso et al 2019). At redshift z = 1.62, Tran et al (2015) find systematically lower star formation rates in the UDS (Ultra-Deep Survey) proto-cluster galaxies compared to the field galaxies, indicating a tentative effect of environment albeit not statistically significant.…”
Section: Introductionmentioning
confidence: 95%
“…In the low-redshift universe (z < 0.2), high-density or cluster environment show a higher fraction of quenched galaxies and have galaxies with lower gas fractions compared to low-density or field environ-ment (Couch et al 2001;Gomez et al 2003;Kauffmann et al 2004;Blanton 2006;Lewis et al 2008;Chung et al 2009;Ellison et al 2009;Barsanti et al 2018;Grootes et al 2018;Koyama et al 2013;Davies et al 2019). The frequency of lenticular and elliptical galaxies increases, and the frequency of spiral galaxies de-creases with the local density indicating that environment affects the morphology of galaxies (Dressler 1980;Van Der Wel et al 2009;Sobral et al 2011;Houghton 2015;Paulino-Afonso et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The morphology-density relation may also be controlled by the change of the ratio between red and blue galaxies. Similar with the SSFR-density relation, it is found that the morphology-density relation in the local universe implies that the environment can also shape the morphologies of galaxies (Dressler 1980;Goto et al 2003;Bamford et al 2009;Skibba et al 2009), which still maintains at higher redshift (van der Wel et al 2007;Tasca et al 2009;Kovač et al 2010;Nantais et al 2013;Allen et al 2016;Krywult et al 2017;Paulino-Afonso et al 2019). By a mean SFR for each morphology types, Poggianti et al (2008) predict the SFR-density relation by using the morphology-density relation (the fractions of the morphological types as a function of density).…”
Section: Discussionmentioning
confidence: 73%